Ablative brain surgery: an overview. (1st October 2019) - Franzini, Andrea; Moosa, Shayan; Servello, Domenico; Small, Isabella; DiMeco, Francesco; Xu, Zhiyuan; Elias, William Jeffrey; Franzini, Angelo; Prada, Francesco
Abstract: Background: Ablative therapies have been used for the treatment of neurological disorders for many years. They have been used both for creating therapeutic lesions within dysfunctional brain circuits and to destroy intracranial tumors and space-occupying masses. Despite the introduction of new effective drugs and neuromodulative techniques, which became more popular and subsequently caused brain ablation techniques to fall out favor, recent technological advances have led to the resurgence of lesioning with an improved safety profile. Currently, the four main ablative techniques that are used for ablative brain surgery are radiofrequency thermoablation, stereotactic radiosurgery, laser interstitial thermal therapy and magnetic resonance-guided focused ultrasound thermal ablation. Object: To review the physical principles underlying brain ablative therapies and to describe their use for neurological disorders. Methods: The literature regarding the neurosurgical applications of brain ablative therapies has been reviewed. Results: Ablative treatments have been used for several neurological disorders, including movement disorders, psychiatric disorders, chronic pain, drug-resistant epilepsy and brain tumors. Conclusions: There are several ongoing efforts to use novel ablative therapies directed towards the brain. The recent development of techniques that allow for precise targeting, accurate delivery of thermal doses and real-time visualization of induced tissue damage during the procedure have resulted in novel techniques for cerebral ablation such as magnetic resonance-guided focused ultrasound or laser interstitial thermal therapy. However, older techniques such as radiofrequency thermal ablation or stereotactic radiosurgery still have a pivotal role in the management of a variety of neurological disorders.